Simulation to Teach Nursing Students About End-of-Life Care. Issue 6 (December 2016) - Hjelmfors, Lisa; Strömberg, Anna; Karlsson, Katarina; Olsson, Louise; Jaarsma, Tiny
Abstract : There is minimal education on death and dying in undergraduate nursing programs, leaving the students unprepared to provide sufficient care to dying patients and their families. This article describes a teaching innovation on how end-of-life care simulation can provide a successful and appreciated learning situation for nursing students, teaching them communication skills in challenging situations. Modifications in the setup of the simulation might help the students to focus more on communication and existential issues instead of mostly practical ones.